EVOLUTION OF MALE COLORATION DURING A POST‐PLEISTOCENE RADIATION OF BAHAMAS MOSQUITOFISH (GAMBUSIA HUBBSI). (1st February 2014) - Martin, Ryan A.; Riesch, Rüdiger; Heinen‐Kay, Justa L.; Langerhans, R. Brian
Abstract: Sexual signal evolution can be complex because multiple factors influence the production, transmission, and reception of sexual signals, as well as receivers' responses to them. To grasp the relative importance of these factors in generating signal diversity, we must simultaneously investigate multiple selective agents and signaling traits within a natural system. We use the model system of the radiation of Bahamas mosquitofish ( Gambusia hubbsi ) inhabiting blue holes to test the effects of resource availability, male body size and other life‐history traits, key aspects of the transmission environment, sex ratio, and predation risk on variation in multiple male color traits. Consistent with previous work examining other traits in this system, several color traits have repeatedly diverged between predation regimes, exhibiting greater elaboration in the absence of predators. However, other factors proved influential as well, with variation in resource levels, body size, relative testes size, and background water color being especially important for several color traits. For one prominent signaling trait, orange dorsal fins, we further confirmed a genetic basis underlying population differences using a laboratory common‐garden experiment. We illustrate a promising approach for gaining a detailed understanding of the many contributing factors in the evolution of multivariate sexual signals.